Faktor Determinan Status Hidrasi Pada Remaja Usia 15-18 Tahun Di SMA Negeri Balung - Aji Permana, Roby; Rosalini, Wike (Nursing Sciences Journal, 2024)
Hydration status in adolescents is important in public health. Teenagers who do not get adequate hydration can experience concentration problems, decreased cognitive function, skin problems, metabolic disorders, fatigue, and mood disorders. The aim of this study was to analyze individual characteristic factors, physiological factors and psychological factors on the hydration status of adolescents aged 15-18 years at SMA Negeri Balung. The research design used in this research is correlational analytic with a cross-sectional approach. The sampling technique used in this research is probability sampling, cluster sampling type. The instruments used in this research were questionnaires, tools to measure nutritional status and hydration status. Inferential analysis was carried out bivariately with Spearman correlation and multivariate with linear regression. The bivariate test results showed that the individual characteristic factors were gender (r=0.651, p<0.05), physiological factors, nutritional status (r=0.381, p<0.05), physical activity (r=0.441, p<0.05) , fluid intake (r=0.821, p<0.05) was related to hydration status. Multivariate test results showed that factors related to hydration status included individual characteristics, gender (p<0.05), physiological factors, nutritional status (p<0.05), physical activity (p<0.05), fluid intake (p <0.05). The R square value is 0.607 indicating that individual characteristic factors (gender) and physiological factors (nutritional status, physical activity, fluid intake) can predict 60.7% of the hydration status of Balung State High School students.